Parallelism and non-parallelism in diabetic nephropathy and diabetic retinopathy - Tang, Shanshan; An, Xuedong; Sun, Wenjie; Zhang, Yuehong; Yang, Cunqing; Kang, Xiaomin; Sun, Yuting; Jiang, Linlin; Zhao, Xuefei; Gao, Qing; Ji, Hangyu; Lian, Fengmei (Frontiers in Endocrinology, 2024)
Diabetic nephropathy (DN) and diabetic retinopathy (DR), as microvascular complications of diabetes mellitus, are currently the leading causes of end-stage renal disease(ESRD) and blindness, respectively, in the adult working population, and they are major public health problems with social and economic burdens. The parallelism between the two in the process of occurrence and development manifests in the high overlap of disease-causing risk factors and pathogenesis， high rates of co-morbidity, mutually predictive effects, and partial concordance in the clinical use of medications. However, since the two organs have their unique internal environment and physiological processes, each with specific influencing molecules, and the target organ itself has non-parallelism due to different pathological changes and responses to various influencing factors, this article provides an overview of the parallelism and non-parallelism between DN and DR, to further recognize the commonalities and differences between the two diseases, to provide references for early diagnosis, clinical guidance on the use of medication, and the development of new drugs.